Under-representation of female athletes in research informing influential concussion consensus and position statements: an evidence review and synthesis - D'Lauro, C.; Jones, E. R.; Swope, L.; Anderson, M. N.; Broglio, S.; Schmidt, J. D. (British Journal of Sports Medicine, 2022)
Objective: We aimed to quantify the female athlete composition of the research data informing the most influential consensus and position statements in treating sports-related concussions.Design We identified the most influential concussion consensus and position statements through citation and documented clinician use; then, we analysed the percentage of male and female athletes from each statement`s cited research. Data sources: We searched PubMed on 26 August 2021 with no date restrictions for English language studies using the terms `concussion position statement` and `concussion consensus statement.`Eligibility criteria for selecting studies Based on each statement having multiple statement editions, documented clinician use, and substantial citation advantages, we selected the National Athletic Trainers` Association (NATA, 2014), International Conference on Concussion in Sport (ICCS, 2017) and the American Medical Society for Sports Medicine (AMSSM, 2019). We extracted all cited studies from all three papers for assessment. For each paper analysing human data, at least two authors independently recorded female athlete participant data.Results A total of 171 distinct studies with human participants were cited by these three consensus and position papers and included in the female athlete analyses (93 NATA; 13 ICCS; 65 AMSSM). All three statements documented a significant under-representation of female athletes in their cited literature, relying on samples that were overall 80.1% male (NATA: 79.9%, ICCS: 87.8 %, AMSSM: 79.4%). Moreover, 40.4% of these studies include no female participants at all. Conclusion: Female athletes are significantly under-represented in the studies guiding clinical care for sport-related concussion for a broad array of sports and exercise medicine clinicians. We recommend intentional recruitment and funding of gender diverse participants in concussion studies, suggest authorship teams reflect diverse perspectives, and encourage consensus statements note when cited data under-represent non-male athletes.